2021
DOI: 10.1007/s10157-021-02101-z
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-induced acute renal tubular injury associated with elevation of serum inflammatory cytokine

Abstract: Background Severe acute respiratory syndrome Coronavirus 2 has rapidly spread worldwide, with acute kidney injury (AKI) as one of the manifestations with unknown causal mechanisms. We aimed to investigate tubular injury by assessing tubular markers and their association with the severity of Coronavirus disease 2019 . Methods We examined the associations between laboratory markers and urinary levels of N-acetyl-β-d-glucosaminidase (uNAG), β2-microglobulin (u β2MG), α1-microglobulin (u α1MG), and liver-type fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 23 publications
2
21
0
2
Order By: Relevance
“…Novel urinary biomarkers have been proposed in COVID-19, including urine 11-dehydro-thromboxane B2, 8-hydroxy-2′-deoxyguanosine, and liver-type fatty acid binding protein (L-FABP) levels, all of which were higher in this patient cohort at the time of hospitalization ( 101 ). N-acetyl-β-D-glucosaminidase, β2-microglobulin, α1-microglobulin, and L-FABP, which are all markers of tubular injury, were significantly associated with inflammation, as were IL-6 levels ( 102 ). Indeed, another observational study confirmed the association between pro-inflammatory cytokines, urinary cytokines, and urinary kidney injury markers ( 103 ).…”
Section: Diagnostic and Prognostic Value Of Biomarkersmentioning
confidence: 99%
“…Novel urinary biomarkers have been proposed in COVID-19, including urine 11-dehydro-thromboxane B2, 8-hydroxy-2′-deoxyguanosine, and liver-type fatty acid binding protein (L-FABP) levels, all of which were higher in this patient cohort at the time of hospitalization ( 101 ). N-acetyl-β-D-glucosaminidase, β2-microglobulin, α1-microglobulin, and L-FABP, which are all markers of tubular injury, were significantly associated with inflammation, as were IL-6 levels ( 102 ). Indeed, another observational study confirmed the association between pro-inflammatory cytokines, urinary cytokines, and urinary kidney injury markers ( 103 ).…”
Section: Diagnostic and Prognostic Value Of Biomarkersmentioning
confidence: 99%
“…Clinical studies suggest that about 50% of patients with COVID-19 had proteinuria and hematuria, suggesting a possible glomerular injury [ 29 ]. Abnormal urine analysis was associated with increased inflammatory markers and could be used to predict the overall outcomes in these patients with COVID-19 [ 30 ]. cFSGS has emerged as a distinct pathology associated with SARS-CoV-2-infected patients with proteinuria [ 27 ].…”
Section: Epidemiology and Clinical Presentationsmentioning
confidence: 99%
“…Furthermore, we cannot discard subclinical tubular damage that might be present in patients with rising CK. The use of other specific tubular biomarkers in addition to serum creatinine could be helpful in future studies [ 27 ]. Likewise, the use of myoglobin and an increase in the number of kidney biopsies are needed to confirm our findings and conduct formal risk prediction analyses with new biomarkers.…”
Section: Discussionmentioning
confidence: 99%